MENATA KAWASAN DENGAN PENDEKATAN KONSEP SHARING CITY - Putri, Nyssa Iga; Ellisa, Evawani (Institut Teknologi dan Bisnis Ahmad Dahlan, 2024)
This research is driven by the inquiry: how does the ancient practice of sharing adapt as a cultural norm in contemporary urban environments? Focusing on the Kalimalang area in Bekasi, which was initially designated as a protected zone due to the presence of the Kalimalang canal, the study traces its evolution into a densely populated region, catalyzed by rapid transportation advancements such as the Indonesia-China High-Speed Rail (KCIC) and LRT Line 2. Through comprehensive analysis spanning macro, mezzo, and micro scales, the study investigates the feasibility of integrating the sharing city principle into urban revitalization endeavors for Kalimalang. Employing data triangulation techniques, informed by insights from